Two new eriophyoid mites (Acari: Eriophyoidea) from West Bengal, India - Sur, Surajit; Roy, Sourav; Chakrabarti, Samiran (Zootaxa, 2018)
Two new species of eriophyoid mites viz. Abacarus sundarbanensis n. sp. infesting Pongamia glabra L. (Fabaceae) and Diptilomiopus augustifoliae n. sp. infesting Ambroma augusta (L.) (Sterculiaceae) respectively, are described from West Bengal, India.